(3TQM GdeNJGQ ef eNJGQ TYQ HTGQs - (3dCHi GdWGgQ ESeGYjd Hf CMeO Hf RjGOI Gddg GdJLjHj GdbjQhGfis; (3LYaQ Hf HTGQ GdGSOjs
(3ChdgG (B:s
(3ai LMad JTQb GdCQV GdaVGA Hg cGddjd CfLeg GdbVHGf hGdCSd s
(3BNQgG (B:s
(3bGd ESeGYjd Hf CMeO Hf RjGOg Gddg Edi gGgfG GfJgi GNJjGQfG ajeG hLOfGg ef GdeNJGQ ef TYQ HTGQ hGdMeO ddg hMOg s
(3HBNQ UaMGJgG JYbjHIs
(3OjhGf HTGQ Hf HQO JMbjb eMeO Hf YGThQ GdebOeg (B1/ 105 (3JhfS (B1976s
(3ebGHdI heUMMI Ydi GdCUd Gdefbhd efgGs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs